PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVMENT DIVISION (STAD) TERHADAP KONSENTRASI BELAJAR SISWA PADA PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Azzahra Salsabila, Zingga; Mas Ramadhan , Gilang; Yunita; Suhesti, Nenden (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of students' learning concentration in Indonesian language lessons, which affected the effectiveness of the learning process. One effort to improve students' learning concentration is through the implementation of the Student Teams Achievement Division (STAD) cooperative learning model. This study aimed to determine the effect of the implementation of the STAD cooperative learning model on the learning concentration of fifth-grade elementary school students in Indonesian language subjects. This research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of 44 students divided into an experimental class and a control class using saturated sampling techniques. Data were collected through a learning concentration questionnaire that had met validity and reliability requirements. Data analysis was conducted using normality tests, homogeneity tests, and the Independent Sample t-test. The results indicated that the implementation of the STAD cooperative learning model significantly affected students' learning concentration in Indonesian language subjects. The STAD learning model increased students' participation during the learning process, enabling them to become more focused, active, and collaborative in achieving learning objectives.Keywords: Cooperative Learning, Student Teams Achievement Division (STAD), Learning Concentration, Indonesian Language, Elementary School